2009
DOI: 10.1016/j.pmrj.2008.12.012
|View full text |Cite
|
Sign up to set email alerts
|

The Practice of Physical Medicine and Rehabilitation in subSaharan Africa and Antarctica: A White Paper or a Black Mark?

Abstract: Antarctica is doing fine. Africa is in a crisis. Local medical schools, hospitals doctors, and persons with disability; along with foreign volunteers, aid groups, and policymakers can impact the crisis. However government-specifically national ministries of health-is ultimately responsible for the health and wellbeing of citizens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Approximately 80% of the global population with disabilities resides in the Majority World (United Nations, 2008), yet health and rehabilitation professionals to meet the needs of these people with disability are in short supply (Anyangwe & Mtonga 2007;Gupta, CastilloLaborde, & Landry, 2011;World Health Organization, 2006). Haig, Im, Adewole, Nelson, andKrabek (2009, p. 1036) highlighted this as follows:…”
Section: Under-served Pwcd In Majority World Countriesmentioning
confidence: 99%
“…Approximately 80% of the global population with disabilities resides in the Majority World (United Nations, 2008), yet health and rehabilitation professionals to meet the needs of these people with disability are in short supply (Anyangwe & Mtonga 2007;Gupta, CastilloLaborde, & Landry, 2011;World Health Organization, 2006). Haig, Im, Adewole, Nelson, andKrabek (2009, p. 1036) highlighted this as follows:…”
Section: Under-served Pwcd In Majority World Countriesmentioning
confidence: 99%
“…When we found that there were only 6 PM&R physicians in all of Sub-Saharan Africa, we made a joke of it: 'The White Book on Physical Medicine and Rehabilitation in Africa and Antarctica'. (2). Except the 'joke' was published in 5 journals around the world as a sign of global alarm and has been cited repeatedly in World Health Organization and other policy documents, as a call to strengthen PM&R throughout the world.…”
Section: Editorialmentioning
confidence: 99%
“…The importance of valid epidemiological measures of function cannot be over estimated. Recently, five rehabilitation medicine journals simultaneously published a white paper exposing the complete lack of the specialty of Physical and Rehabilitation Medicine in subSaharan Africa [15]. Members of a community-based rehabilitation consortium debated these findings, claiming that Africa is well served by community-based programmes [16].…”
Section: Scientific and Practical Implicationsmentioning
confidence: 99%